Advantages and disadvantages of dental whitening between 35% hydrogen peroxide for office use and 10% carbamide peroxide for home use. Literature Review - Tacuri Chungata, Jefferson Xavier (2023)
Tooth color change is an alteration that varies in cause, location and severity, which may be related to extrinsic factors, intrinsic factors or a combination of both; For this reason, dental whitening is one of the procedures most requested from dentists; more and more patients are looking for a better image and smile without considering the possible consequences. This is due to the constant advertising in the media; in addition, it has led to the appearance of certain products on the market that are used by consumers without any control from the dentist. Therefore, the objective of this review is to know the advantages and disadvantages of dental whitening with 35% hydrogen peroxide (PH) (ultradent) in the office and 10% carbamide peroxide (PC) (ultradent) for home use, with the aim of in order to guarantee the comfort of patients during use and to avoid possible adverse effects. The academic Google search engine was reviewed, as well as databases: PubMed, SciELO, Medigraphic and ScienceDirect, in the period 2002 to 2020, using as keywords "hydrogen peroxide", "carbamide peroxide", "whitening”, “clarification”, “ph” and their similar in English. Two hundred fifty-four articles were obtained, of which 50 were selected and analyzed because they were related to the topic raised. It is concluded that, according to the instructions specified by the manufacturer, PH 35% and PC 10% are reliable agents for dentistry.